Low-cost implementation of damped harmonic motion for structural vibration studies - Fitria Silviana; Soni Prayogi (Universitas Sebelas Maret, 2025)
This study presents a low-cost experimental approach to investigating damped harmonic motion for structural vibration studies, using easily accessible electronic components and open-source microcontroller technology. The primary objective is to validate the feasibility of accurately capturing and analyzing vibrational behavior through an economical setup, making advanced physics experimentation accessible for educational and research purposes. The system comprises a spring-mass mechanism integrated with sensors such as ultrasonic rangefinders and LDRs connected to an Arduino Uno, allowing real-time data acquisition of displacement, velocity, and acceleration. The experiment begins with an initial phase of gravitational free fall, followed by a transition to damped harmonic oscillation once the spring is activated, triggered at a threshold displacement. Graphical and tabular representations of the motion illustrate the classic underdamped response, including phase-shifted oscillations and exponential decay of amplitude, closely matching theoretical models of second-order dynamic systems. This transition is marked by clear time and displacement boundaries, providing valuable insight into non-ideal spring behavior and real-world mechanical thresholds. The results confirm that key dynamic properties, such as damping ratio and natural frequency, can be qualitatively and quantitatively examined through low-cost means without sacrificing measurement reliability. Overall, the study highlights the pedagogical effectiveness and scalability of such a system in introducing fundamental mechanical vibration concepts. This work contributes to both physics education and applied engineering by promoting affordable, accurate, and adaptable experimental tools for the study of structural dynamics and harmonic motion in real-world scenarios